Intensi Mahasiswa Akuntansi Dalam Pemilihan Jalur Karir: Studi Pada Mahasiswa PPA & PPBP PT Bank Central Asia, Tbk - Arpandie IE, Wendy; Yanti, Yanti (GEMA EKONOMI, 2023)
The purpose of this study is to determine the factors that influence the career paths of accounting students. The population used in this study were accounting students from the Accounting Education Program or the Business and Banking Education Program organized by PT Bank Central Asia, Tbk. The samples taken were 100 people. Selection of the sample using the probability sampling method with simple random sampling technique. The data analysis technique uses Structural Equation Modeling (SEM) which is supported by the SmartPLS 3.0 program. Based on the results of research conducted, the influence of third parties and career exposure has no effect on the career path of accounting students. Meanwhile, intrinsic motivation and extrinsic motivation have an influence on the career paths of accounting students